Incidencia de hemoparásitos en los sistemas productivos en ovinos (Ovis orientalis aries) del Cantón Vinces de la Provincia de Los Ríos - Oleas Torres, Madeley Lilibeth (2023)
The present investigation was carried out in sheep production units in the Vinces canton of the province of Los Ríos. An incidence study was carried out in order to establish whether hemoparasites (Anaplasma ovis, Babesia ovis and Trypanosoma vivax) are found in small ruminants with a traditional breeding system, where (248 sheep) were taken randomly selected from 22 farms located in the Canton Vinces. As a diagnostic method, blood samples were taken from each animal, subsequently the smears were taken to the laboratory, to be observed under the microscope. The results obtained in the laboratory can identify the causal agent of these Hemoparasites, positive cases were 48 samples, which represents 19.35%, and negative cases were 80.64%, which represents 200 samples, giving a total of 248. Hemoparasitic diseases directly affect to sheep production in the Vinces Canton, with an incidence of 28 cases of Anaplasma Ovis, which represents 11.29%, in Babesia Ovis, 15 cases were found, representing 6.04%, in Trypanosoma vivax, 5 cases were found, representing 11.29%. %. Positive cases due to zootechnical characteristics were found in sheep with 18 cases representing 7.31%, lamb 11 cases representing 4.43%, sheep 12 cases representing 4.83%, rams 7 cases representing 2.82%. , of the total sample.